2017
DOI: 10.1016/j.spinee.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a polyetheretherketone (PEEK) titanium composite interbody spacer in an ovine lumbar interbody fusion model: biomechanical, microcomputed tomographic, and histologic analyses

Abstract: Overall, the results indicate that PTC interbody devices could potentially lead to a more robust intervertebral fusion relative to a standard PEEK device in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 35 publications
3
69
0
Order By: Relevance
“…36 In this instance, bioactive substances, in particular microstructured Ti, have been shown to improve the biocompatibility of PEEK interbody cages and to increase the rate of bone fusion. 37 Unlike PEEK that has an elastic modulus similar to bone, Ti material has an elastic mismatch that can lead to stress shielding and bone remodeling around the implant. 38,39 In this study, there was no difference in subsidence rates between Ti and PEEK cages.…”
Section: Discussionmentioning
confidence: 99%
“…36 In this instance, bioactive substances, in particular microstructured Ti, have been shown to improve the biocompatibility of PEEK interbody cages and to increase the rate of bone fusion. 37 Unlike PEEK that has an elastic modulus similar to bone, Ti material has an elastic mismatch that can lead to stress shielding and bone remodeling around the implant. 38,39 In this study, there was no difference in subsidence rates between Ti and PEEK cages.…”
Section: Discussionmentioning
confidence: 99%
“…Malposition and loosening of pedicle screw are main reasons of failure of internal xation. The reported rate of pedicle screw malposition is 5-41% [15][16][17]. Numerous studies have proved the in uencing factors of the pullout strength [18][19].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that Ti-Peek inter-body devices could potentially lead to a more robust intevertebral fusion relative to a standard PEEK device (Figure 4). 19 On the other hand, we have studies which contradict to a good results of composite spacers. Predominant problem may be wear debris and delamination caused by shear loading.…”
Section: Titanium-polyetheretherketone Composite Cagesmentioning
confidence: 91%